Germany : Financial Sector Assessment Program-Fund Management: Regulation, Supervision and Systemic Risk Monitoring-Technical Notes. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses the German asset management sector and an analysis of certain key aspects of the regulatory and supervisory regime. Germany has a large and diverse asset management sector to which it applies a strong and comprehensive regulatory framework. The sector is the third-largest in Europe, as measured by all managed assets, and comprises a broad range of management companies and funds. BaFin is able to monitor developments in the asset management sector by having access to an extensive set of data shared by the Bundesbank. The data are sufficiently granular that individual exposures can be identified swiftly and accurately, allowing supervisory intervention where needed.